Molecular Studies Of Vibrio Cholerae Strains Isolated From Local Outbreak - Wan Mohd. Zain, Wan Somarny (2003)
Cholera caused by toxigenic Vibrio cholerae is a major public health problem in developing countries. Epidemiology surveillance of cholera and comparative analysis of strains collected during outbreaks has demonstrated clonal diversity among epidemic strains and a continual emergence of new clones of toxigenic V. cholerae. In the present study, the Random Amplified polymorphic DNA (RAPD) technique was performed to study the clonal diversity on twenty isolates of V cholerae and five isolates of V. harveyi (as a comparison). Eighteen of V cholerae isolates belong to the Ogawa serotypes, while two isolates were Inaba and 0139 Bengal serotypes, respectively. Fourteen out of twenty random primers yielded clear and reproducible bands. From the RAPD banding profiles, the polymorphism rates of bands were much higher between V cholerae and V harveyi than those found among V cholerae isolates. According to the dendrogram generated from the RAPDistance software program,